Advancing cancer care and prevention in the Caribbean: a survey of strategies for the region. Issue 9 (September 2019) - Spence, Dingle; Argentieri, M Austin; Andall-Brereton, Glennis; Anderson, Benjamin O; Duggan, Catherine; Bodkyn, Curt; Bray, Freddie; Gibson, Tracey; Garcia, Wendy Gomez; Greaves, Natalie; Gupta, Sumit; Hobday, Virginia; et al.
Summary: Cancer is now the second leading cause of death in the Caribbean. Despite this growing burden, many Caribbean small island nations have health systems that struggle to provide optimal cancer care for their populations. In this Series paper, we identify several promising strategies to improve cancer prevention and treatment that have emerged across small island nations that are part of the Caribbean Community. These strategies include the establishment of a Caribbean cancer registry hub, the development of resource-appropriate clinical guidelines, innovations in delivering specialty oncology services (eg, paediatric oncology and palliative care), improving access to opioids, and developing regional training capacity in palliative medicine. These developments emphasise the crucial role of public–private partnerships in improving health care for the region and show how fostering strategic collaborations with colleagues and centres in more developed countries, who can contribute specialised expertise and improve regional collaboration, can improve care across the cancer control continuum.